To solve for t, let's first combine like terms on both sides of the equation:
16 - 2t = t + 9 + 4t
Combine the terms with t:
16 - 2t = 5t + 9
Next, let's isolate the t terms on one side of the equation by subtracting 5t from both sides:
16 - 2t - 5t = 5t + 9 - 5t
Combine the t terms:
16 - 7t = 9
Next, let's isolate the constant term on one side by subtracting 16 from both sides:
16 - 7t - 16 = 9 - 16
Simplify:
-7t = -7
Finally, let's solve for t by dividing both sides by -7:
-7t/-7 = -7/-7
Simplify:
t = 1
Therefore, the solution to the equation is t = 1.
16-2t=t+9+4t
solve for t
1 answer